Effect of oral antiseptic agents on phospholipase and proteinase enzymes of Candida albicans - GÜMRÜ TARÇIN, BİRSAY; KADİR, TANJU (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
Objective: Candida-associated denture stomatitis is the most prevalent form of oral candida infections among the denture wearers. Generally, antiseptic oral rinses used in the treatment of these infections are considered as an adjunct or alternative antifungal treatment. Studies have suggested that the intraoral concentrations of antiseptics decrease substantially to the sub-therapeutic levels on account of the dynamics of the oral cavity. This condition yields the question about the minimum antiseptic concentration that effect the character or pathogenesis of Candida during treatment. The extracellular phospholipase and proteinase enzymes of Candida albicans are regarded to have a crucial role in the pathogenesis of human fungal infections. Therefore, the aim of this study was to investigate the effect of different sub-therapeutic concentrations of chlorhexidine gluconate, hexetidine and triclosan on the production of these enzymes by C. albicans strains isolated from 20 patients with denture stomatitis. Methods: Phospholipase test was done by using Sabouraud dextrose agar with egg yolk, proteinase test was done by using bovine serum albumin agar. Methods: Phospholipase test was done by using Sabouraud dextrose agar with egg yolk, proteinase test was done by using bovine serum albumin agar. Results: Exoenzyme production of 20 strains which were brief exposured to sub-therapeutic concentrations of three antiseptic agents decreased significantly compared with the strains that were not exposured with antiseptic values (p < 0.05). There was significant difference between the sub therapeutic concentrations of each of three antiseptics (p < 0.05). When the same concentrations of each antiseptic was compared, there were no significant differences between enzymatic activities (p > 0.05). Conclusions: The results of this study show that sub-therapeutic levels of each antiseptic may modulate candidal exoenzyme production, consequently suppressing pathogenicity of C albicans. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Candida-associated denture stomatitis; Chlorhexidine; Hexetidine; Triclosan; Exoenzymes; BUCCAL EPITHELIAL-CELLS; GERM TUBE FORMATION; CHLORHEXIDINE GLUCONATE; IN-VITRO; SUBTHERAPEUTIC CONCENTRATIONS; VIRULENCE FACTORS; BRIEF EXPOSURE; SACCHAROMYCES-CEREVISIAE; DENTURE STOMATITIS; MOUTH RINSES